Allergen immunotherapy for allergic asthma: a systematic review and meta-analysis - Dhami, Sangeeta; Pfaar, Oliver (Allergy, 2017)
Background To inform the development of the European Academy of Allergy and Clinical Immunology's (EAACI) Guidelines on Allergen Immunotherapy (AIT) for allergic asthma, we assessed the evidence on the effectiveness, cost-effectiveness and safety of AIT. Methods We performed a systematic review, which involved searching nine databases. Studies were screened against predefined eligibility criteria and critically appraised using established instruments. Data were synthesized using random-effects meta-analyses. Results 98 studies satisfied the inclusion criteria. Short-term symptom scores were reduced with a standardized mean difference (SMD) of −1.11 (95% CI −1.66, −0.56). This was robust to a prespecified sensitivity analyses, but there was evidence suggestive of publication bias. Short-term medication scores were reduced SMD −1.21 (95% CI −1.87, −0.54), again with evidence of potential publication bias. There was no reduction in short-term combined medication and symptom scores SMD 0.17 (95% CI −0.23, 0.58), but one study showed a beneficial long-term effect. For secondary outcomes, subcutaneous immunotherapy (SCIT) improved quality of life and decreased allergen-specific airway hyperreactivity (AHR), but this was not the case for sublingual immunotherapy (SLIT). There were no consistent effects on asthma control, exacerbations, lung function, and nonspecific AHR. AIT resulted in a modest increased risk of adverse events (AEs). Although relatively uncommon, systemic AEs were more frequent with SCIT; however no fatalities were reported. The limited evidence on cost-effectiveness was mainly available for sublingual immunotherapy (SLIT) and this suggested that SLIT is likely to be cost-effective. Conclusions AIT can achieve substantial reductions in short-term symptom and medication scores in allergic asthma. It was however associated with a modest increased risk of systemic and local AEs. More data are needed in relation to secondary outcomes, longer-term effectiveness and cost-effectiveness.